Synthesis and In vitro Cytotocxic Evaluation of New Quinazolinone Derivatives - Thinh, Tran Dang; Vu, Tran Khac (VNU Journal of Science: Natural Sciences and Technology, 2020)
The paper presents a simple and efficient synthesis of a series of new quinazolinone derivatives 8a-h . First, the reaction of 5-hydroxyanthranilic acid ( 6 ) with acetic anhydride at 160–180oC for 2 h gave the intermediate 7 in high yield. This intermediate was then reacted with amines in acetic acid at 180 oC for 14 h afforded new quinazolinone derivatives 8a-h in 77–92%. Synthesized compounds were structurally confirmed using spectroscopic methods: 1 H, 13 CNMR and mass spectrum. The bioassay result using three cancer cell lines including SKLU-1 (lung cancer), MCF-7 (breast cancer) and HepG-2 (liver cancer) showed that only compound 8h exhibited significant cytotoxic effect against cancer cell lines tested with IC50 values of 23.09, 27.75 and 30.19 µg/ mL, respectively.